Edukasi Pertolongan Pertama Gawat Darurat (PPGD) Sebagai Penguat Keterampilan Pada Siswa SMP - Nabila Ramadhani Muchtar; Hasmi Nur Bayhaqi; Moch. Hasan Sidqi; Mila Hariani; Didit Darmawan (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
This research aims to explore the role of Emergency First Aid (PPGD) education as a tool to strengthen life skills in junior high school (SMP) students. PPGD education is very important to equip students with the basic knowledge and skills needed in emergency situations. At the junior high school level, many students still do not understand how to handle emergency situations, so this educational program is designed to increase their readiness to respond to various emergencies quickly and effectively. This research also highlights challenges in implementing the PPGD curriculum, such as availability of resources, teacher training, and effectiveness of teaching methods. In addition, the level of awareness of students and schools about the importance of PPGD skills was also analyzed, considering that low understanding can hinder the effectiveness of this program. It is hoped that the results of this research can make a significant contribution to improving students' life skills through more integrated health education in schools. PPGD education that is successfully implemented is expected to make junior high school students better prepared to face emergency situations, and able to provide fast and appropriate first aid.